Analisis Kualitas Air Sumur Dangkal di RK 4 Kelurahan Doom Barat Distrik Sorong Kepulauan - Yasin, Azalia Fajri; Dwangga, Mierta; Mardin, Firmansyah (Program Studi Magister Manajemen Lingkungan, 2024)
Doom Island is a small island in Southwest Papua Province, Indonesia. Located right across from Sorong City, clean water services from PDAM do not yet reach all of Dum Island, so some people on Doom Island still use dug wells or shallow wells. The aim of this research is to determine the influence of sea water, the status of quality standards on the quality of shallow well water in RK 4, West Doom village, and the solution to its influence is to build an absorption well. The sampling technique uses purposive sampling intentionally, determining water quality status using the storet method. The results of the research at sample points 1 - 14, at sample points 1 - 3 there is the influence of sea water on shallow well water with a distance from the shoreline of around 13 - 22 meters with a shallow well depth of around 5 - 6 meters below the ground surface, with a value salinity 1180 – 2130 mg/L. The high salinity test value resulted in the influence of sea water in shallow wells at several well points in RK 4 West Doom Village. On average, most of the shallow wells in RK 4 West Dum District have class B water quality status, namely lightly polluted.